Uma introdução ao estudo das derivadas no ensino médio - Silva, Eliseu do Nascimento (Universidade Federal Rural do Semi-Árido, 2016)
This is a bibliographic research that examines, through a literature review, the results of the introduction, in high school, the notions of limits and derivatives, applied to the study of the functions of the 1st and 2nd degrees, kinematics, studies geometric solids and analytical geometry, in order to understand these contents in order to prepare future students for the discipline of Calculus Differential and Integral in higher education. The overall objective of the research was to identify the importance of the applications of the derivative in high school. The outlined specific objectives were to address in mathematical language the meaning of derivative; demonstrate the rules of Derivation and highlight the usefulness of the derivative as a rate of change. It presents a sequence of steps to enter the intuitive ideas of concurrent limit and derivatives with the above mentioned contents. The theoretical basis used to give the research were: Geraldo Ávila, Louis Leithold, George F. Simmons, James Stewart, among others. As a result, it was found that one can introduce the basics of limit and derivatives in high school, in various mathematical content, in order to reduce the dropout and failure in discipline Differential and Integral Calculus, recurring in various courses higher level. It is noted that there is need for further research on this theme in order to highlight the importance of the introduction of differential calculus notions in high school. Calls to students and teachers, math lovers, deepen and provide for those who are entering the school world the breadth of applications of derivative and mathematics so they can arouse the interest of students for learning limits and derivatives
Keywords: Coeficiente angular; Limite; Derivada; Função do 1° grau; Função do 2° grau; Máximo; Mínimo; Angular coefficient; Limit; Derived; Function of the 1st degree; Function of 2nd degree; Maximum; Minimum; CIENCIAS EXATAS E DA TERRA::MATEMATICA